Radiolabeled Compounds for Diagnosis and Treatment of Cancer - Kumar, Krishan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Radiopharmaceuticals are used in the diagnosis and treatment of various diseases, especially cancer. In general, radiopharmaceuticals are either salts of radionuclides or radionuclides bound to biologically active molecules, drugs, or cells. Tremendous progress has been made in discovering, developing, and commercializing numerous radiopharmaceuticals for the imaging and therapy of cancer. Significant research is ongoing in academia and the pharmaceutical industry to develop more novel radiolabeled compounds as potential radiopharmaceuticals for unmet needs. This Special Issue aims to focus on all aspects of the design, characterization, evaluation, and development of novel radiolabeled compounds for the diagnosis and treatment of cancer and the application of new radiochemistry and methodologies for the development of novel radiolabeled compounds. Outstanding contributions presented in this Special Issue will significantly add to the field of radiopharmaceuticals.